Risk factors of postoperative nausea and vomiting following ambulatory surgery: A retrospective case-control study. Issue 12 (December 2022) - Qian, Yue; Zhu, Jian-kun; Hou, Bai-ling; Sun, Yu-e; Gu, Xiao-ping; Ma, Zheng-liang
Abstract: Objective: To explore potential risk factors of postoperative nausea and vomiting (PONV) following ambulatory surgery. Method: Clinical data of 1670 cases receiving ambulatory surgery in Nanjing Drum Tower Hospital, the Affiliated Hospital of Nanjing University Medical School from September 2017 to December 2019 were retrospectively analyzed. They were categorized to PONV group and non-PONV group, and perioperative data in both groups were analyzed for assessing risk factors of PONV following ambulatory laparoscopy. Results: There were 156/1, 670 (9.3%) PONV cases, and the female and male incidence in recruited cases was 12.0% and 6.0%, respectively. Analyses on perioperative data of them identified that female gender [adjusted odds ratio (aOR) = 2.060, P < 0.001], operation time >1 h (aOR = 1.554, P = 0.011), postoperative pain at rest (aOR = 1.909, P = 0.013) and postoperative pain during activities (aOR = 3.512, P < 0.001) were independent risk factors of PONV following ambulatory surgery. Furthermore, postoperative pain at rest and during activities were linearly, positively correlated to the incidence of PONV. Conclusion: Female gender, operation time >1 h and postoperative pain are closely related with the incidence of PONV following ambulatory surgery. Alleviating postoperative pain properly is one of the methods to reduce risk factors of PONV following ambulatory surgery. Abstract : Postoperative nausea and vomiting; Ambulatory surgery; Postoperative pain.